An assessment of the current status of integration of palliative care into primary health care centers in Alexandra community - Soogun, Olusoji (Department of Public Health and Family Medicine, 2020)
Introduction-The WHA resolution in 2014 to strengthen PC as a continuum of health care service delivery mandated member states to incorporate PC into their NHS using the PHS. An assessment of a health system will only be complete when the four elements of the PHS that (entrenches palliative care) are assessed alongside preventative, curative and rehabilitative care. Aim-To assess the current status of integration of PC into the PHC centers in Alexandra community in Johannesburg, South Africa. Objectives - 1) to identify the existing policies including budgets available in the clinics relating to PC, 2) to identify the availability of PC essential medicines in the PHC and 3) to survey the HCPs training in PC. Methodology- Each objective has different targets. Objective number 1) has clinic managers as its targets. Objective 2), HCPs and people involved in procuring and prescribing essential medications and objective 3), all the HCPS. Data was collected using structured questionnaires administered by the researcher and analyzed using statistical tables. Results-The clinic mangers are not aware of NPFSPC, there is no provincial policy, budget or any existing policy on PC in any of the clinics. The essential medicines are available in the clinics, only recent graduates has undergraduate trainings in PC, no HCP has any post graduate training in PC at any level (Certificate, Diploma or Masters) as recommended by the WHA resolution to member countries. Skills in PC is close to zero in the PHCs. Conclusion-The study confirm the findings in previous literature and highlights the needs for PC policies and continuous training in PC for HCPs, essential medicines for PC are in the clinics contrary to findings in other LMIC.